Cognitive sociolinguistics language variation, cultural models, social systems - Kristiansen, Gitte 1966-; Dirven, René 1932-2016 (Mouton de Gruyter, 2008)
A union of Cognitive Linguistics and Sociolinguistics was bound to happen. Both proclaim a usage-based approach to language and aim to analyse actual language use in objective ways. Whereas Sociolinguistics is by nature on the outlook for language in its variety, CL can no longer afford to ignore social variation in language as it manifests itself in the usage data. Nor can it fail to adopt an empirical methodology that reflects variation as it actually occurs, beyond the limited knowledge of the individual observer. Conversely, while CL can only benefit from a heightened sensitivity to social
Keywords: Soziolinguistik; Kognitive Linguistik; Aufsatzsammlung